Octupole vibrations and ground state correlations - Hernández, E. S. (1975)
The relationship between ground-state correlations and collectiveness is investigated for the case of low-lying nonrotational states in the rare earth nuclei. Both octupole and quadrupole modes of excitation are studied and the quasiparticle virtual populations associated with each of them are discussed. The relative importance of particle-particle and particle-hole interaction matrix elements is also analyzed in connection with the shape of the correlation patterns. The fundamental role of the Nilsson + BCS scheme is emphasized and the consistency of the quasiparticle random-phase approximation is established.